Teaching colonial history and national identity development among palestinian students in Israel : resisting colonisation through student activism - Makkawi, Ibrahim (CLACSO, 2021)
This research project explores the colonial hegemony and pedagogical contradictions embedded within the process of collective-national identity development among Palestinian students in the Israeli formal educational system through inductive examination of the dialectical interplay between the three agents of the formal educational process; namely, the formal curriculum, the students, and the teachers. The study utilised Grounded Theory (Glaser & Strauss, 1967) as a qualitative research method and used three sets of data: (a) the formal curriculum of history used in grades 7-12 in Palestinian schools in Israel, (b) in-depth qualitative interviews with 7 History Palestinian teachers who are officially employed by the Israeli government and teach Palestinian students in the segregated Palestinian schools in Israel, (c) in-depth interviews with 14 Palestinian college students who are graduates of this formal educational system. The three sets of data were analyzed separately, then compared and contrasted to depict an overall picture of the findings of the study.